Reactive power reserve margin management for voltage improvement using evolutionary programming optimization technique / Azahar Zullkepli - Zullkepli, Azahar (2007)
Reactive power reserve margin management in power system is important in order to obtain their maximum voltage improvement. This project presents Evolutionary Programming (EP) optimization technique as the application shows that after the optimal reactive power rescheduling, the reactive power of the system will be increased and at the same time voltage will be improved. Several fitness functions such as total power loss minimization and voltage profile improvement has been explored through the implemented Evolutionary Programming optimization technique. The proposed technique was tested with IEEE 30-Bus Test System and the programmed were developed using MATLAB software